Characterisation of mucosal associated invariant T-cells and MR1 in ruminants - Goldfinch, Nicholas Graham (The University of Edinburgh, 2010)
Mucosal associated invariant T-cells (MAIT) are a phylogenetically conserved subset of alpha/beta T-cells with natural killer-like (NK) activity. MAIT are defined by the expression of an invariant T-cell receptor alpha (TCRα) chain; in mice and humans this chain uses the orthologous mVα19/hVα7.2-Jα33 genes respectively. Available evidence indicates that MAIT are restricted by MR1, a highly conserved MHC class I-related molecule, and that their development is dependent on B lymphocytes. They appear to constitute part of the innate immune response, but their precise functional role is poorly understood. This study aimed to characterise MAIT and MR1 in ruminants, and to further the knowledge and understanding of these unique cells. Using PCR primers based on partial database sequences, orthologous full-length TCRα chains were identified in circulating bovine and ovine T cells. The germline elements of the respective α chains were identified and their overall frequency of expression within the bovine TCRα repertoire determined. Experiments using the orthologous TCRα chain as a marker for MAIT cells to examine expression in bovine and ovine blood and various tissues showed that spleen and mesenteric lymph nodes contained the highest frequency of MAIT cells. Use of the same technique to study levels of this marker in cattle of different ages revealed very low numbers of MAIT cells in neonatal animals, followed by a marked increase in the first 3 weeks of life. Analyses of MAIT TCRα expression in different T cell subsets showed that, unlike mice and humans in which MAIT cells are predominantly within the CD4-/CD8- T-cell population, MAIT cells in bovine blood are predominantly CD8+. Full-length cDNAs were isolated for bovine and sheep MR1 and their sequences were found to display marked cross-species conservation. Using a specific PCR, MR1 was shown to be expressed in peripheral blood and by different lineages of Theileria-transformed cells. Alternatively-spliced transcripts of MR1 were detected in both cattle and sheep and several of these retained an intact open-reading frame. Constructs of bovine MR1 and an MR1/MHC chimera were prepared in a eukaryotic expression vector but these failed to give detectable cell surface expression following transfection into Cos-7, despite positive intracellular expression.
Keywords: T cell receptor; MRI; MAIT; Mucosal associated invariant T-cells; mucosal immunology; non-classical MHC; ruminant